Interprofessional education using simulation of an overnight inpatient ward shift. Issue 3 (May 2015) - Joyal, Kristina M.; Katz, Cara; Harder, Nicole; Dean, Heather
Abstract In healthcare it is rare for professionals to practice together before they practice together. Nightmare Night Care is an annual interprofessional voluntary event for health sciences students in nursing, medicine and pharmacy to come together for a simulated hospital overnight ward shift. The purpose of this study was to investigate the interprofessional knowledge, skills and attitudes the students learn from this experience. Students responded to surveys before (n = 45) and after the event (n = 11) regarding their understanding of the goals of interprofessional education (IPE), roles and responsibilities of other professions, and what they learned from this event. Responses demonstrated that students are eager to learn in interprofessional settings and that IPE events may aid in building understanding and communication between professions. IPE events are an opportunity to allow students to learn about each other; however, they must occur frequently, and must include an orientation on role clarification if they are to have an effect on changing preconceived stereotypes of the other professions.